SNHG1 promotes proliferation, migration and invasion of bladder cancer cells via the PI3K/AKT signaling pathway - Du, Quan (Exp Ther Med, 2020)
Long non-coding RNA (lncRNA) small nucleolar RNA host gene 1 (SNHG1) has been previously reported to mediate a number of functions during the progression of cancer. However, its involvement in bladder cancer remain unclear. The aim of the present study was to investigate the expression of SNHG1 in bladder cancer and to identify its potential mechanisms. SNHG1 expression was firstly detected in cancer tissues and cells. The effects of SNHG1 on the malignant phenotypes were then investigated. Furthermore, the influence of SNHG1 on the PI3K/AKT signaling pathway was examined. It was demonstrated that SNHG1 expression was significantly upregulated in bladder cancer tissues and cells. Moreover, the loss-of-function experimental results suggested that knockdown of SNHG1 inhibited bladder cancer cell proliferation, migration and invasion, but increased apoptosis; however, SNHG1 overexpression promoted these processes. Mechanistically, rescue assays identified that SNHG1 activated the PI3K/AKT signaling pathway. Therefore, it was speculated that SNHG1 functioned as a carcinogenic lncRNA in bladder cancer via activation of PI3K/AKT.